Analysis of the Implementation of the Independent Learning Curriculum in Informatics Subjects for Class VIII Students of Smpk Santo Yoseph Naikoten, Kupang City - Firdolina, Firdolina; Neno, Khatrin J. Taku; Fallo, Diana Y.A. (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to describe: 1) to analyze the implementation of the independent curriculum in Informatics learning for class VIII SMPK Santo Yoseph Naikoten, Kupang City 2) to analyze the obstacles and barriers in implementing the independent curriculum in Informatics learning for class VIII SMPK Santo Yoseph Naikoten, Kupang City, 3) to analyze efforts to overcome obstacles and barriers in implementing the independent curriculum in Informatics learning for class VIII SMPK Santo Yoseph Naikoten, Kupang City.This research is a qualitative research. The research was conducted at SMPK Santo Yoseph Naikoten, Kupang City in July 2024. The subjects of this study were the Principal, Class VIII Teachers, and Class VIII Students. Data collection techniques were carried out using observation, interviews and documentation. Activities in qualitative data analysis using interactive models, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that: 1) the implementation of the independent curriculum in Informatics learning has been realized well, the planning carried out is by analyzing CP, compiling TP, and making ATP. The implementation of learning has implemented differentiated learning that is adjusted to student needs and has compiled evaluations in the form of diagnostic assessments, formative and summative assessments, 2) there are obstacles and barriers such as less valid information, reference sources are still few, limited time in compiling teaching modules and assessments, 3) efforts made to overcome obstacles and barriers are by participating in seminars, webinars and workshops, increasing reference sources and utilizing the teaching module preparation guidebook provided by the government.